A translation from "Pavan" into English of Angelo Beolco's Parlamento de Ruzante, qual giera sto in campo : Ruzante's Discourse on coming back from the battlefield : a re-edition of a famous Italian 16th century play based on Verona Civica ms. 36 - Ruzzante, 1502?-1542 (Edwin Mellen Press, 2012)
The present study is divided into three parts, the first of which is an in-depth introduction by Carlo Fanelli to the authors and problems of 16th century Renaissance Italian dialect comedy and the relevance of a playwright such as Angelo Beolco (RUZANTE). Particular attention is paid to the comedy from the point of view of the social problems presented by veterans or deserters after long and socially disastrous wars. The second part is a short introduction to the manuscript history of RUZANTE's dialect comedy El Parlamento prior its printing by Stefano Alessi at Venice in 1551. The Verona Cod.